2015
DOI: 10.1186/s40657-015-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of coastal wetlands of international importance for waterbirds: a review of China Coastal Waterbird Surveys 2005–2013

Abstract: Background: China's coastal wetlands belong to some of the most threatened ecosystems worldwide. The loss and degradation of these wetlands seriously threaten waterbirds that depend on wetlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 11 publications
4
108
0
Order By: Relevance
“…The Yalujiang Estuary Wetlands (hereafter YLE), located in the northern Yellow Sea, support over 150,000 shorebirds in the pre-breeding stopover period annually (Barter et al 2000;Riegen et al 2014;Bai et al 2015). Those birds, especially large-to mediumsized shorebirds, such as Eurasian Curlew (Numenius arquata), Bar-tailed Godwit, Great Knot, and Grey Plover (Pluvialis squatarola) use this tidal flat as an important refueling site (Bai et al 2015;Choi et al 2015Choi et al , 2017. Satellite-tracking records show that YLE is also the final pre-breeding stopover site for Bar-tailed Godwits (of both races menzbieri and baueri) (Battley et al 2012) and Great Knots (Lisovski et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Yalujiang Estuary Wetlands (hereafter YLE), located in the northern Yellow Sea, support over 150,000 shorebirds in the pre-breeding stopover period annually (Barter et al 2000;Riegen et al 2014;Bai et al 2015). Those birds, especially large-to mediumsized shorebirds, such as Eurasian Curlew (Numenius arquata), Bar-tailed Godwit, Great Knot, and Grey Plover (Pluvialis squatarola) use this tidal flat as an important refueling site (Bai et al 2015;Choi et al 2015Choi et al , 2017. Satellite-tracking records show that YLE is also the final pre-breeding stopover site for Bar-tailed Godwits (of both races menzbieri and baueri) (Battley et al 2012) and Great Knots (Lisovski et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1D). Populations of more than 50% of bird species are falling, and at least 27 are endangered (6). The plight of the red-crowned crane (Grus japonensis) is clearly due to habitat loss.…”
mentioning
confidence: 99%
“…There are already very large windfarms along parts of the Jiangsu and Liaoning coasts and the world's first intertidal windfarm, with 58 turbines and a generating capacity of 150 MW (Anon. 2015b), has been developed at Rudong, Jiangsu Province, in the area that supports much of the global population of Spoon-billed Sandpiper during both northward and southward migration, as well as internationally important populations of another 14 species of wader (Bai et al 2015;Fig. S17 in Supplementary material).…”
Section: Windmentioning
confidence: 99%
“…Despite major changes to many coastal areas surveyed by Mark Barter (Yang et al 2011), and reported declines in many shorebird populations within the East Asian-Australasian Flyway (Amano et al 2010;Rogers et al 2011;Wilson et al 2011;MacKinnon et al 2012;Australian Government 2015aChoi et al 2015;Hansen et al 2015), current surveys by Fudan University (Y. Chen, unpublished data) and the China Coastal Waterbird Census team (Bai et al 2015;Hua et al 2015) show that almost the entire soft shore of China's Yellow Sea coast meets Ramsar listing criteria as either staging sites, wintering grounds or breeding grounds, this being reflected in current proposals for designating 'red lines' (L. Zhang et al, unpubl. data).…”
Section: Introductionmentioning
confidence: 99%